2014
DOI: 10.4025/imagenseduc.v4i3.25739
|View full text |Cite
|
Sign up to set email alerts
|

Saberes tradicionais sobre plantas medicinais: interfaces com o ensino de botânica

Abstract: Resumo Este artigo apresenta resultados de uma intervenção pedagógica baseada no diálogo entre saberes tradicionais e científicos em sala de aula, objetivando investigar de que forma as plantas consideradas medicinais e comumente utilizadas pelos moradores da comunidade quilombola Furnas do Dionísio (Jaraguari/MS), podem contribuir para uma apropriação significativa de conteúdos de Botânica pelos alunos do ensino médio da escola da comunidade. Foram realizadas entrevistas e aplicados formulários junto aos mora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
1
0
5
Order By: Relevance
“…Beyond the aforementioned lack of research on integrating medicinal herbs into environmental education in Central Europe (except Malatinszky, 2007;Azevedo et al, 2015), we identified interesting experiences in the Latin American dialogues on critical environmental pedagogy after Paulo Freire and Enrique Leff that address the intertwined environmental and educational crises (e.g., de Oliveira Martins and Ramos Araujo, 2021) and successfully integrate traditional knowledge of medicinal plants into rural school biology curricula in southern Brazil (Vinholi Júnior and Gonçalves de Azevedo, 2020). There is evidence that this practice reduces the distance both between school and regional culture and between school and everyday life, preserving cultural identity, traditional knowledge of medicinal plants, their meaning, symbolism, magic and reality (Vinholi Júnior and Vargas, 2014;Vinholi Júnior and Vargas, 2015;Souza Silva and Santos Baptista, 2018;Sousa et al, 2022;Ursi et al, 2018). In addition, the use of medicinal plants as an "educational tool" increases environmental literacy, including species knowledge, and uses the school's immediate environment as a triple didactic resource: First, to explore and discover the world through observation and contact; second, as a starting point for the development of integrated learning projects; and third, as a means to transform desires and feelings into active proposals, opportunities to change reality, and meaningful learning as a basis for emancipated citizenship (Säumel et al, 2017;Vinholi Júnior and Gonçalves de Azevedo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the aforementioned lack of research on integrating medicinal herbs into environmental education in Central Europe (except Malatinszky, 2007;Azevedo et al, 2015), we identified interesting experiences in the Latin American dialogues on critical environmental pedagogy after Paulo Freire and Enrique Leff that address the intertwined environmental and educational crises (e.g., de Oliveira Martins and Ramos Araujo, 2021) and successfully integrate traditional knowledge of medicinal plants into rural school biology curricula in southern Brazil (Vinholi Júnior and Gonçalves de Azevedo, 2020). There is evidence that this practice reduces the distance both between school and regional culture and between school and everyday life, preserving cultural identity, traditional knowledge of medicinal plants, their meaning, symbolism, magic and reality (Vinholi Júnior and Vargas, 2014;Vinholi Júnior and Vargas, 2015;Souza Silva and Santos Baptista, 2018;Sousa et al, 2022;Ursi et al, 2018). In addition, the use of medicinal plants as an "educational tool" increases environmental literacy, including species knowledge, and uses the school's immediate environment as a triple didactic resource: First, to explore and discover the world through observation and contact; second, as a starting point for the development of integrated learning projects; and third, as a means to transform desires and feelings into active proposals, opportunities to change reality, and meaningful learning as a basis for emancipated citizenship (Säumel et al, 2017;Vinholi Júnior and Gonçalves de Azevedo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Para Venholi Junior e Vargas (2014) [24] ao inserir conhecimentos populares sobre plantas medicinais nas salas de aula, abrem-se oportunidades para o diálogo entre saberes trazidos pelo educando e o saber científico. Kovalski et al (2011) [25] reiteram que os conhecimentos adquiridos pelos alunos são construídos no seu cotidiano e, por isso, precisam ser abordados no currículo escolar, porém tal conhecimento é deixado de lado.…”
Section: Tabela 2: Frequências Absolutas (Fa) E Relativas (Fr) Da Regunclassified
“…As populações tradicionais brasileiras (Scudeller;Veiga;Araújo-Jorge, 2009), tais como as indígenas Marisco, 2016), as quilombolas (Vinholi Júnior, 2016), os caboclos (Flor;Barbosa, 2015), os ribeirinhos (Modro et al, 2015), os caiçaras (Giraldi;Hanazaki, 2010) e os "mateiros" (moradores de regiões florestais, conhecedores da flora e fauna local e de seus usos), se utilizam de ervas e plantas medicinais para o tratamento e cura de doenças. Esses conhecimentos, que formam um saber popular tradicional, são transmitidos através das gerações, principalmente entre os membros das famílias e, hodiernamente, mediante a troca de informações pelas redes sociais (Ricardo, 2009).…”
Section: Introductionunclassified